A padronização e classificação de fruta como ferramenta de gestão : um estudo na comercialização de pêssego e nectarina. - Dornfeld, Hugo Carlos (Universidade Federal de São Carlos, 2007)
The objective of this dissertation is to evaluate the use of standardization and classification rules, suggested by the CEAGESP, by peach and nectarine producers and wholesalers and identify the effects of this procedure in the supplying and commercialization of the mentioned fruits. The methodology used was the qualitative study and the study case, where the procedure adopted for the information survey was the interviews with producers from two cities of the São Paulo state and with the wholesalers of the Entreposto Terminal de São Paulo (ETSP). Differences were found among the producers from Guapiara and Paranapanema, which the first region is formed of simpler producers without access of information or any kind of technology. Most producers of the second region are optimist about the use of standardization and classification rules and emphasizes that its use is the reason of the peach and nectarine commercialization success, by this, they invest in the improvement of fruit quality by updating, when possible, the technologies used in the production and post-harvest processes. This way, the use of standardization and classification rules helps and provides more benefits than disadvantages to those producers that adopt it. In relation to the wholesalers, it was identified the preference and valorization of classified peach and nectarine, although these agents says that the market does not yet recognize the proper benefits of the use of standardization and classification rules. The conclusion of this dissertation is that use of standardization and classification rules suggested by the CEAGESP works as a tool to help the management of peach and nectarine commercialization process
Keywords: Frutas - cultivo; Normas; Classificação; Classification; Commercialization; Peach; Nectarine; Rural producers; Wholesaler market; ENGENHARIAS::ENGENHARIA DE PRODUCAO